Hypomethylating agent alters the immune microenvironment in acute myeloid leukaemia (AML) and enhances the immunogenicity of a dendritic cell/AML vaccine. (3rd March 2019) - Nahas, Myrna R.; Stroopinsky, Dina; Rosenblatt, Jacalyn; Cole, Leandra; Pyzer, Athalia R.; Anastasiadou, Eleni; Sergeeva, Anna; Ephraim, Adam; Washington, Abigail; Orr, Shira; McMasters, Malgorzata; Weinstock, Matthew; et al.
Summary: Acute myeloid leukaemia (AML) is a lethal haematological malignancy characterized by an immunosuppressive milieu in the tumour microenvironment (TME) that fosters disease growth and therapeutic resistance. Hypomethylating agents (HMAs) demonstrate clinical efficacy in AML patients and exert immunomodulatory activities. In the present study, we show that guadecitabine augments both antigen processing and presentation, resulting in increased AML susceptibility to T cell‐mediated killing. Exposure to HMA results in the activation of the endogenous retroviral pathway with concomitant downstream amplification of critical mediators of inflammation. In an immunocompetent murine leukaemia model, guadecitabine negatively regulates inhibitory accessory cells in the TME by decreasing PD‐1 (also termed PDCD1) expressing T cells and reducing AML‐mediated expansion of myeloid‐derived suppressor cells. Therapy with guadecitabine results in enhanced leukaemia‐specific immunity, as manifested by increased CD4 and CD8 cells targeting syngeneic leukaemia cells. We have previously reported that vaccination with AML/dendritic cell fusions elicits the expansion of leukaemia‐specific T cells and protects against disease relapse. In the present study, we demonstrate that vaccination in conjunction with HMA therapy results in enhanced anti‐leukaemia immunity and survival. The combination of a novel personalized dendritic cell/AML fusion vaccine and an HMA has therapeutic potential, and a clinical trial investigating this combination is planned.